21 Cases of Cororectal Lateral Spreading Tumor - Simada, A.; Asou, S.; Takano, M.; Hidaka, H.; Toyohara, T.; Nozaki, R.; Kuromizu, J.; Inoue, F.; Tashiro, K.; Nakashima, E.; Kubota, I.; Tokumine, F.; et al. (Nippon Daicho Komonbyo Gakkai Zasshi, 1997)
The 21 cases (22 lesions) of colorectal lateral spreading tumors (LST) were studied. These lesions were called carpet-like tumor, creeping tumor, nodule-aggregating tumor and non-nodule-aggregating flat elevation. In this paper, clinicopathlogical features of those tumors were described. The conclusions were as follows : (a) Nodule-aggregating type LST may show malignant change with increasing size and height of the nodule. (b) There was no difference in malignant potential between nodule-aggregating type LST and non-nodule-aggregating type LST. (c) End-oscopic resection may be indicated in less than 30mm nodule-aggregating type and less than 10mm non nodule-aggregating type.